PENGGARUH MODEL TWO STAY TWO STRAY TERHADAP HASIL BELAJAR PKN DI SEKOLAH DASAR - Rezeki, Sri; Rosnita, Rosnita; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research to analyze the effect of model learning two stay two stray towards the results of learning and knowing the magnitude of the influence model of learning two stay two stray towards the results of studying Civics class V primary school South Pontianak 36 country. The method used is an experiment with the shape of the Experimental Design types Quasy non equivalent control group design. The results of the data analysis the average post-test and experiment control class is 68.61 and 79.14. Based on the results of a test of normality of the data using the formula Chi Squared Gaussian data. Furthermore its homogeneity test data done by Fhitung (1.79) < Ftabel (1.94), homogeneous and expressed continued test-t with the formula separated variance, acquired thitung (3.378) > ttabel (2.042) and dk = 39, so the Ha is received. From the results of the calculation of effect size, obtained ? ? amounting to 0.75 criteria are. Conclusion this study is a model of learning two stay two stray influence is being against the results of studying Civics class V 36 State primary school South Pontianak. Keywords : Two Stay Two Stray, The Result Of The Study, Citizenship Education